Integrating Science Experimentation in Teaching Mathematics: A Lesson Study - G. Baybayon, Gilbert; Beth E. Clemente, Winnie; Catherine Eco, Patricia; Rose P. Rosquita, Mary; B. Zamora, Christian; E. Elipane, Levi (International Journal of Engineering and Technology, 2018)
Integrated science and mathematics education provide meaningful learning to the students through different strategies such as the use of real-life activities in the classroom. This study focuses on how science experimentation can be integrated in mathematics through process integration approach. To determine how science integration in the teaching of mathematics lesson can be successful, the researchers conducted a lesson study that enables planning, observing, analyzing, and refining the â€˜research lessonâ€™ on integrating the two discipline. Themes on the implementation of the research lesson were identified and were given suggestions to come up with a more established lesson.Â Â